Konsep Implementasi Manajemen Pendidikan Islam dan Ekonomi Syariah di Asia Tenggara - Nurul Fazirah Harahap; Chuzaimah Batubara (Universitas Muhammadiyah Enrekang, 2023)
This determination aims to understand the image and campaign of Islam and Islamic teachings. Economic Administration in Southeast Asia, where this important lesson is the curriculum of the Islamic curriculum and Islamic economics in Indonesia and Malaysia. The allocation method determines the order in which additional bibliographies are allocated using a repository approach. With the help of structure and content approach, the image and practice of Islamic teachings are developed. Islamic economic domination in Southeast Asia (Indonesia and Malaysia) is expected to increase significantly. Thoughts about the various beliefs found and spread over the last hundred years. The results show that there are rare similarities between the views and practices of Islamic education and Islamic business. Indonesia and Malaysia are geographically close together, so that through a historical period the direction was determined by the international civilization hierarchy. Another thing that creates closeness is that the two countries are developing an Islamic economy which is still very strong today.